Over a million students use our free study notes to help them with their homework
y1 = -3x2- 9x + 30 , y2 = x2 + 3x - 10Equate two curves ( y1 = y2 )Obtain following simplified quadratic: x2 + 3x + 10 = 0Facto...
To solve this problem I would begin by rearranging the first equation to equal X.1) x + y = 1 -> x = 1 - yI would then substitute this into the second equation.2) 2x + 3y = 9 -> 2(1-y) + 3y = 9Then ...
This is a question from Higher Tier and involves 1) realising that 2nd difference is a constant: 6. 2) knowing that constant 2nd difference implies the sequence is quadratic. 3) remembering or proving tha...
Recall that the general term in the binomial expansion of (x+y)^n is (nCr)(x^n-r)(y^r), so by the binomial theorem, the entire expansion is the sum of these terms from r = 0 to n. In this case, n = 33, th...
←
606
607
608
609
610
→
Internet Safety
Payment Security
Cyber
Essentials